-5x(x+2)=-(-5x+1)-x

Simple and best practice solution for -5x(x+2)=-(-5x+1)-x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5x(x+2)=-(-5x+1)-x equation:



-5x(x+2)=-(-5x+1)-x
We move all terms to the left:
-5x(x+2)-(-(-5x+1)-x)=0
We multiply parentheses
-5x^2-10x-(-(-5x+1)-x)=0
We calculate terms in parentheses: -(-(-5x+1)-x), so:
-(-5x+1)-x
We add all the numbers together, and all the variables
-1x-(-5x+1)
We get rid of parentheses
-1x+5x-1
We add all the numbers together, and all the variables
4x-1
Back to the equation:
-(4x-1)
We get rid of parentheses
-5x^2-10x-4x+1=0
We add all the numbers together, and all the variables
-5x^2-14x+1=0
a = -5; b = -14; c = +1;
Δ = b2-4ac
Δ = -142-4·(-5)·1
Δ = 216
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{216}=\sqrt{36*6}=\sqrt{36}*\sqrt{6}=6\sqrt{6}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-14)-6\sqrt{6}}{2*-5}=\frac{14-6\sqrt{6}}{-10} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-14)+6\sqrt{6}}{2*-5}=\frac{14+6\sqrt{6}}{-10} $

See similar equations:

| 5a+9+6a=35 | | -7(-2+3x)=203 | | 3(x+6)=4(x-13) | | z/5+80=88 | | -4(2x+3)=-(6x-20) | | 28.24=6g+3.58 | | -7/8=-3/4x+1/3 | | X=32m2 | | 5x-1+7-13+6x-4=13 | | 6u−36=-42 | | 9+4n=15-n | | 2r-18=-2 | | 2x-7=137-2x | | h+5.7=-5.7 | | 6x+6=-150-7x | | 5x-16+2x=7x-2 | | 3q-6(q-8)=42 | | 2n+5+6=1+7n | | 5(-6f)+13)=35 | | 1.5x+2.5-1.5=0.5x+3 | | h+26=839 | | -3+-2h=1 | | −25=k−17 | | 4-2(3x-5)=-40 | | 13-x=3+7x | | -4b+8+6b+2=b+1+6 | | 10x+3=2(5x)+3 | | A.10b+8b+9−18b+3=5+6b−2b−12+7 | | 2.2x=-8.8 | | 2x+24=x+19 | | 4x+6=9-4x | | 2x-7=-7+7x |

Equations solver categories